(untitled) (Dordrecht (The Netherlands), 2008)
This book presents the new EU approach to environmental management and its attempt to place it in the perspective of sustainable development. China and other large and fast growing economies are putting increasing pressures on global environment, but they are also looking at the European experience with great interest. To critically present this experience can help those countries avoid the mistakes made by developed countries in dealing with the relation between economic growth and environmental protection, and to improve the institutions and tools for better environmental governance.
Keywords: Sustainable development,Environmental management,Environmental policy